Um estudo sobre memória e consciência política em diálogos Intergeracionais - Borella, Joel Fernando (2019)
This thesis is linked to the Nucleus of Research in Political Psychology and Social Movements (NUPMOS) of the Post Graduate Studies Program in Social Psychology of the Pontifical Catholic University of São Paulo (PUC-SP). In a society in which the narrative presents itself in scarcity, by a veiled social project of forgetting and silencing of voices, works with memory is a necessary process of affirmation and belonging of the subjects in their means. In this sense, this research has as objective, besides deepening studies on memory, political memory and political consciousness, to use intergenerational meetings in focus groups to foment psycho-political practices in Psychology that potentiate spaces of social interactions, exchange of experiences, affections and foundations for the construction of dialogues on Brazilian political history and the current political moment in Brazil. To this end, 4 focus groups were organized in a higher education institution (ISE) with people between the ages of 18 to 76 years old. Twelve classrooms were visited, totaling 243 students from courses of Psychology, Law, Nursing, Agronomy, Civil Engineering, Architecture and Administration. Of these, 9 students had interest and 6, at the end of the procedures of the invitation participated. Each participating student would invite another member (younger or older) who had proximity to the political issue throughout the history of this relationship. We then totaled 12 participants. We divided the groups on the first day into: On the first day, we divided them into: 1st Focus group of the younger participants; 2nd Focus Group with the older participants. And on the second day 3rd and 4th intergenerational meeting. The focus groups lasted between 90 minutes and 120 minutes and were recorded in audiovisual devices to facilitate transcriptions. The methodology we use transits between the qualitative approach, Focus Groups, intergenerationality, analyzes of political memory and the dimensions of political consciousness. We divided into three macro categories: Group 1 - the younger; Group 2 – older; Group 3 and 4 - Intergenerational meetings; and subcategories containing issues such as generational conflicts, Fake News, Political Climate, Corruption, social movements, memory and forgetfulness, military dictatorship, political changes, political memory, intergenerationality, and political consciousness. It is possible to develop psychopolitical analysis that show the power of memory in group work, the importance of knowing the history of Brazil through the speech of the subjects and their experiences and exercising the analytical processes of political consciousness and political memory in intergenerational groups, (re)building the past and instigating coping strategies for the present and for a less threatening, more democratic and intergenerational future